The Influence of Compensation and Work Environment on Employee Retention with Job Satisfaction as an Intervening Variable (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
This research aims to determine the effect of compensation and work environment on employee retention through job satisfaction as an intervening variable at CV Berkah Surya Abadi. The researcher used primary data obtained by distributing questionnaire forms using Google Form to employees at CV Berkah Surya Abadi. The technique used was a saturated sample (census), namely all employees of CV Berkah Surya Abadi. The analysis tool used in this study used SmartPLS 4. The results of this study are that compensation and work environment do not have a significant effect on employee retention, job satisfaction has a positive and significant effect on employee retention, compensation and work environment have a positive and significant effect on job satisfaction, job satisfaction has a significant effect mediating the effect of compensation on employee retention and job satisfaction has a significant effect mediating the effect of work environment on employee retention.
Keywords: Compensation; Work Environment; Employee Retention; Job Satisfaction